Analysis of the correlation between EAT thickness and prognosis in patients with heart failure with preserved ejection fraction - Ma, Jianfei; Zhang, Hongbin; Ma, Ting; Liu, Fei (Frontiers in Cardiovascular Medicine, 2025)
PurposeTo explore the correlation between epicardial adipose tissue (EAT) thickness and prognosis in patients with heart failure with preserved ejection fraction.MethodA total of 156 patients diagnosed with heart failure with preserved ejection fraction (HFpEF) were selected as the observation group. Another 150 healthy persons undergoing physical examination were selected as the control group. According to the 1-year follow-up results of prognosis of HFpEF patients, they were further divided into a good prognosis group (112 cases) and a poor prognosis group (44 cases).ResultThe EAT thickness, left ventricular mass index (LVMI), left atrial diameter (LAD), and left ventricular end-diastolic diameter (LVEDD) of HFpEF patients in the observation group were higher than those of the control group, and their LVEF was lower than that of the control group. EAT thickness was negatively correlated with LVEF, and EAT thickness was positively correlated with LVMI, LAD, and LVEDD. Hemoglobin and estimated renal glomeruli of the poor prognosis group were lower than those of the good prognosis group. The EAT thickness, blood lactate, and serum creatinine in the poor prognosis group were higher than those in the good prognosis group. Reduced hemoglobin, increased EAT thickness, and increased blood lactate were risk factors for poor prognosis in patients with HFpEF. The receiver operating characteristic analysis showed that the optimal EAT cutoff value was 5.65 mm (area under the curve = 0.892, 95% CI = 0.833–0.936), with 89.13% sensitivity and 88.39% specificity. For the Kaplan–Meier survival analysis, when performing the post hoc stratification of event-free survival, we applied a clinician-relevant threshold of 7.59 mm.ConclusionEAT thickness is inversely related to HFpEF severity and reflects left ventricular remodeling. EAT thickness may be a potentially useful non-invasive prognostic indicator of poorer outcomes in patients with HFpEF.